2023
DOI: 10.3390/ijms24043922
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Photoinactivation of Fusarium oxysporum Conidia with Light-Activated Ammonium Phthalocyanines

Abstract: Antimicrobial photodynamic therapy (aPDT) has been explored as an innovative therapeutic approach because it can be used to inactivate a variety of microbial forms (vegetative forms and spores) without causing significant damage to host tissues, and without the development of resistance to the photosensitization process. This study assesses the photodynamic antifungal/sporicidal activity of tetra- and octasubstituted phthalocyanine (Pc) dyes with ammonium groups. Tetra- and octasubstituted zinc(II) phthalocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…With a concentration of 1 µM of PS, and similar irradiation conditions (light dose of 486 J.cm −2 ), a significant inactivation could be observed with all tested PSs, except for PS 1, which represents the first evidence of the lower efficiency of this PS, in comparison with the other molecules. An estimate of the minimum inhibitory concentration (MIC) of thiopyridinium or ammonium phthalocyanines against conidia, pointed to values of 5 to 60 µM [38,39]. Therefore, assays conducted with a concentration of 1 µM may be interpreted as representing sub-lethal conditions, and allow the comparative assessment of the different PSs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With a concentration of 1 µM of PS, and similar irradiation conditions (light dose of 486 J.cm −2 ), a significant inactivation could be observed with all tested PSs, except for PS 1, which represents the first evidence of the lower efficiency of this PS, in comparison with the other molecules. An estimate of the minimum inhibitory concentration (MIC) of thiopyridinium or ammonium phthalocyanines against conidia, pointed to values of 5 to 60 µM [38,39]. Therefore, assays conducted with a concentration of 1 µM may be interpreted as representing sub-lethal conditions, and allow the comparative assessment of the different PSs.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of differences in the photosensitization efficiency, which can be related to 1 O 2 generation capacity and the effect of the number of charges on solubility and affinity towards the spore material, all PSs have been shown to be effective against Fusarium oxysporum conidia at concentrations above 10 µM. Other studies of the photoinactivation of Fusarium oxysporum conidia with the use of ammonium phthalocyanines as photosensitizers needed higher concentrations of PS such as 40 and 60 µM at the same light doses [38]. The study found that quaternized derivatives were highly effective as photosensitizers and required only a concentration of 1 µM to significantly inactivate Fusarium oxysporum conidia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations